A Classroom Action Research: How to Improving Students Science Process Skill using Problem-Based Learning Models - Azzubairiyah, Nurul; Trimulyono, Guntur; Hikmah, Ziyadatul (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
The 21st century requires science process skills, yet class 7-B students at UPT SMPN 10 Gresik have not engaged in learning activities that enhance these skills. This is a classroom research study that aims to improve students' science process skills, especially observing, predicting, interpreting, concluding, and communicating, by applying a problem-based learning model. We identified the classroom problem and the plan for the research, collected data by implementing a problem-based learning model, and analyzed and interpreted the data. If the students' science process skills have not reached the expected level, we must reflect and revise the plan. Student worksheets to facilitate problem-based learning in the study. The research sample comprised 32 students in class 7-B UPT SMPN 10 Gresik. We collect data using pretest and posttest science process skills. We analyzed and classified the obtained data using the guidelines for categorizing science process skills. The results showed that the average percentage of students' science process skills in the pre-cycle was 16.0 in the very poor category. In cycle II, the average percentage of science process skills rose to 39.1 in the poor category. Then, in cycle II, the average percentage of students' science process skills was 77.8 in the good category. These findings indicated that the problem-based learning model can improve science process skills. So, science learning activities should use a problem-based learning model so teachers can practice their students’ science process skills.